Effect of a mixture of bovine milk oligosaccharides, Lactobacillus rhamnosus NCC4007 and long‐chain polyunsaturated fatty acids on catch‐up growth of intra‐uterine growth‐restricted rats. (8th August 2013) - Castañeda‐Gutiérrez, E.; Moser, M.; García‐Ródenas, C.; Raymond, F.; Mansourian, R.; Rubio‐Aliaga, I.; Viguet‐Carrin, S.; Metairon, S.; Ammon‐Zufferey, C.; Avanti‐Nigro, O.; Macé, K.; Silva‐Zolezzi, I.
Abstract Aim To investigate the effect of a nutritional mixture (bovine milk oligosaccharides, Lactobacillus rhamnosus NCC4007, arachidonic and docosahexaenoic acid) on growth of intrauterine growth‐restricted (IUGR) rats. Methods IUGR was induced by maternal food restriction. The offspring (males and females) were assigned to: REF (non‐IUGR, no mixture), IUGRc (IUGR, no mixture), or IUGRmx (IUGR, mixture). The mixture was given from day 7 to day 58, when tissues and plasma from half of the animals were collected for hormones, metabolites and microarray analysis. The rest received a high‐fat diet (HFD) until day 100. Glucose tolerance was measured at 56 and 98 days, and body fat content at 21, 52 and 97 days. Results IUGRmx had the greatest growth during lactation, but from day 22 to day 54, both IUGR groups gained less body weight than the REF (P < 0.05). In the short‐term (58 days), IUGRmx tended to be longer (P = 0.06) and had less body fat (P = 0.03) than IUGRc. These differences were not seen after HFD. Microarray analysis of hepatic mRNA expression at 58 and 100 days revealed a gender‐dependent treatment effect, and expression of genes related to lipid metabolism was the most affected. Twelve of these genes were selected for studying differences in DNA methylation in the promoter region, for some, we observed age‐ and gender‐related differences but none because of treatment. Conclusion The nutritional intervention promoted catch‐up growth and normalized excessive adiposity in IUGR animals at short‐term. The benefits did not extend after a period of HFD. IUGR and early diet had gender‐dependent effects on hepatic gene expression.